Design de eletrodos em nanoescala visando o desenvolvimento de supercapacitores de alto desempenho - Moreira, Thamyres Fernandes Messa (Universidade Estadual Paulista (Unesp), 2025)
Throughout this project, we utilized the Quantum Rate Spectroscopy (QRS) technique to examine the electronic structure of graphene-derived nanofilms in a 2D configuration at room temperature. This method allowed us to avoid the complexity of vacuum conditions, making it both efficient and cost-effective. Our research centered on the supercapacitance phenomena in reduced graphene oxide structures from a quantum mechanical rate theory perspective. While traditional views primarily link supercapacitance in carbon materials to electrostatic capacitance, which depends on surface area, our findings reveal that quantum rate theory introduces an overlap between electrostatic and chemical (quantum) capacitance states. This discovery provides a more detailed understanding of the energy dynamics within these materials. In exploring these quantum capacitance states, we uncovered an energy overlap between the electrostatic and quantum capacitive energy levels in reduced graphene oxide. Our results show that the charge dynamics in these structures adhere to a quantum resistance limit, consistent with quantum electrodynamics principles. This research sheds light on a new aspect of electron behavior in nanoscale carbon structures, offering signif icant insights into the unique properties of graphene-based materials and their potential applications in energy storage. Building on the foundational understanding gained from our studies of 2D nanostructures, we advanced to the development of 3D symmetric supercapacitors. This was achieved by incorporating functional groups and redox-active molecules, such as p-phenylenediamine (PPD), to modify graphene derivatives, enhancing their suitability as symmetric electrodes in supercapacitor devices. The achievements of this project are substantial, highlighted by the submission of a paper titled The Quantum Mechanical Origin of the Supercapacitance Phenomenon in Reduced Graphene Oxide Structures to the Carbon journal. Additionally, five other papers are nearing completion, further emphasizing the importance of this work.
The Nanoscale Designing of Electrodes Aimingat the Development of High-Performance Supercapacitors
Keywords: Supercapacitores; Energia